2018
DOI: 10.1159/000489244
|View full text |Cite
|
Sign up to set email alerts
|

UCP3 Ablation Exacerbates High-Salt Induced Cardiac Hypertrophy and Cardiac Dysfunction

Abstract: Background/Aims: Excessive salt intake and left ventricular hypertrophy (LVH) are both critical for the development of hypertension and heart failure. The uncoupling protein 3 (UCP3) plays a cardio-protective role in early heart failure development. However, the potential role for UCP3 in salt intake and LVH is unclear. Methods: UCP3-/- and C57BL/6 mice were placed on either a normal-salt (NS, 0.5%) or a high-salt (HS, 8%) diet for 24 weeks. The cardiac function, endurance capacity, energy expenditu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Previous research suggests that LVH enhanced cardiovascular diseases related mortality and morbidity (Lang et al., 2018 ; Wang et al., 2019 ). It is proofed that the CVD risk factors are linked with the expansion of LVH.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous research suggests that LVH enhanced cardiovascular diseases related mortality and morbidity (Lang et al., 2018 ; Wang et al., 2019 ). It is proofed that the CVD risk factors are linked with the expansion of LVH.…”
Section: Discussionmentioning
confidence: 96%
“…In the meantime, increased BP level plays a crucial role in activating LV myocardial expansion via chronic hemodynamic overload and enhanced central pressure. Primary hypertension disease in which environmental and genetic factors interact, with the fat intake being a significant environmental marker (Lang et al., 2018 ; Wang et al., 2019 ). Various studies on the animals and epidemiological surveys have exhibited a positive correlation between the BP level and fat intakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its mechanism is adjusting energy homeostasis though thermogenesis and regulating ROS release [28]. The association between UCPs and hypertension was discovered in lab studies [29,30], and was verified in Asian population [31,32]. Molecular epidemiology studies found UCP2 polymorphism alters the risk of developing CAD in some populations [33,34], while the relation between UCPs and obesity was widely recognized in several populations [35][36][37].…”
Section: Discussionmentioning
confidence: 97%